Effects of Translanguaging in Online Peer Feedback on Chinese University English-as-a-Foreign-Language Students' Writing Performance. (August 2022) - Paul Sun, Peijian; Jun Zhang, Lawrence
Peer feedback has long been recognized for its value in improving second language learning outcomes. However, limited attention has been given to the potential influence of translanguaging in the process of online peer feedback on learners' second language writing performance. To fill the gap, we carried out this mixed-methods study to examine to what extent translanguaging in online peer feedback contributes to improvement in second language writing performance. A total of 79 Chinese English-as-a-foreign-language university students participated in 3 rounds of online peer feedback with a control group using only second language English ( n = 39) and an experimental group adopting translanguaging ( n = 40) in the process of online peer feedback. Six semi-structured interviews were also carried out to solicit participants' understanding of online peer feedback. The quantitative results revealed that translanguaging online peer feedback, compared to English-only online peer feedback, was significantly more conducive to the improvement of learners' second language writing performance in the first round of online peer feedback. However, such a significant difference was not observed in the second and third rounds of online peer feedback. The qualitative findings, on the other hand, showed that both conditions of online peer feedback were supported for their own advantages of improving learners' second language writing. Additionally, the qualitative findings suggested that factors, such as motivation, agency, self-efficacy and translanguaging awareness, should be taken into consideration to enhance students' translanguaging practice.